The Water-Energy Nexus at City Level: The Case Study of Skiathos - Alexandra E. Ioannou (Proceedings, 2018)
Water and energy are two inextricably linked resources of great importance, as they are the key for satisfying basic human needs. In this study a water–energy nexus analysis is conducted in order to achieve a sustainable supply and effectively manage water and energy at city level. Different electricity uses such as domestic, agricultural and commercial are compared and tested on how they correlate with water use. Moreover, time series of water and energy consumption for the island of Skiathos are analyzed using specific distance metrics. The results of the analysis show that water and energy are intimately related.